2016
DOI: 10.1016/j.antiviral.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-based control of tick-borne flavivirus neuropathogenesis: Challenges and perspectives

Abstract: In recent years, microRNA-targeting has become an effective strategy for selective control of tissue-tropism and pathogenicity of both DNA and RNA viruses. Previously, we reported the successful application of this strategy to control the neurovirulent phenotype of a model chimeric tick-borne encephalitis/dengue type 4 virus (TBEV/DEN4), containing the structural protein genes of a highly virulent TBEV in the genetic backbone of non-neuroinvasive DEN4 virus. In the present study, we investigated the suitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…To address this, first we modified 2×511(T) to increase miRNA target stability and prevent formation of escape mutants under miRNA-mediated selective pressure (S3 Fig). Previously, we showed that insertion of multiple copies of miRNA targets into distant regions of flavivirus genome minimizes the probability of formation of escape mutants, which may be capable of infecting cells expressing these miRNAs [47][48][49]. Correspondingly, we introduced duplicated capsid gene region (dCGR) into genome of 2×511(T) virus and inserted two additional target sequences for mir-511-3p between two copies of capsid protein gene, generating C/3'NCR-511(T) virus (Fig 6A and S6 Fig).…”
Section: Targeting Multiple Regions Of Zikv Genome For Mir-511-3p Inhmentioning
confidence: 99%
“…To address this, first we modified 2×511(T) to increase miRNA target stability and prevent formation of escape mutants under miRNA-mediated selective pressure (S3 Fig). Previously, we showed that insertion of multiple copies of miRNA targets into distant regions of flavivirus genome minimizes the probability of formation of escape mutants, which may be capable of infecting cells expressing these miRNAs [47][48][49]. Correspondingly, we introduced duplicated capsid gene region (dCGR) into genome of 2×511(T) virus and inserted two additional target sequences for mir-511-3p between two copies of capsid protein gene, generating C/3'NCR-511(T) virus (Fig 6A and S6 Fig).…”
Section: Targeting Multiple Regions Of Zikv Genome For Mir-511-3p Inhmentioning
confidence: 99%
“…The available data on abundant host microRNAs (116,117) enable the design of target sites along with various virus genomes specific for host microRNAs (118,119). One major disadvantage of virus attenuation by this strategy is the instability of the target miRNA sequence in the modified genome, which can result in a reversion of the virus to the virulent phenotype, although several results on counterstrategies were reported (120)(121)(122). Other approaches offer replication-defective, chimeric vaccines, in which parts of the TBFV genome are replaced by homologous genomic regions derived from a heterologous (e.g., mosquito-borne) flavivirus.…”
Section: Prevention Control and Treatmentmentioning
confidence: 99%
“…Isolated in 1950s from ixodid ticks in Malaysia 16 , this virus did not appear to be associated with human diseases and, unlike most members of TBEV complex, requires only biosafety level 2 biocontainment. Moreover, LGTV is being considered as a genetic platform for development of live attenuated vaccines against neurotropic tick-borne flaviviruses 17 18 19 , underscoring relevance of the virus for vaccine research.…”
mentioning
confidence: 99%